The system of diagnostics of bankruptcy threat to the enterprises - Bivainis, Juozas; Garškaitė, Kristina (Business: Theory and Practice, 2010)
The prepared system of diagnostics of bankruptcy threat to the enterprises, is presented in the article. Herein, bankruptcy, threatening the enterprises, is being diagnosed as per three stages, i.e. the condition of the enterprise and the reasons, which have determined such condition, are being gradually concretized. The financial condition of the enterprises and the threat of bankruptcy are being evaluated at the first stage by applying the integrated model, which assists in achieving the generalized evaluation of the condition. The relative financial indices of the enterprise are being analysed at the second stage, seeking for diagnosing the problematic fields of the enterprise. The third stage, at which the absolute financial indices are being analysed, is aimed at ascertaining the reasons, which have determined the condition of the enterprise. The size of the crisis, the crisis factors of activity are ascertained by taking into consideration the evaluation indices of the condition of the enterprise; they allow selecting substantially the bankruptcy prevention measures out of the possible leading set of internal and external measures. The possibilities of adaptation of the prepared system of diagnostics to the enterprises, which are attributed to various economic sectors and to the changing environmental conditions, are foreseen. Article in Lithuanian. Įmonių bankroto grėsmės diagnostikos sistema Santrauka. Straipsnyje aprašyta parengta įmonių bankroto grėsmės diagnostikos sistema. Pagal ją įmonių bankroto grėsmės diagnostika atliekama trimis etapais, palaipsniui konkretinant įmonės būklę ir ją sukėlusias priežastis. Pirmajame etape fi-nansinė įmonių būklė ir bankroto grėsmė vertinama taikant integruotą modelį, pagal kurį gaunamas apibendrinantis būklės įvertis. Antrajame etape analizuojami santykiniai finansiniai įmonės rodikliai, siekiant diagnozuoti problemines įmonės sritis. Trečiojo etapo, kuriame analizuojami absoliutiniai finansiniai rodikliai, paskirtis – nustatyti įmonės būklę lėmusias priežastis. Gauti įmonės būklės įverčiai leidžia pagrįstai parinkti bankroto prevencijos priemones iš galimų orientacinio vidinių ir išorinių priemonių rinkinio. Numatytos parengtos diagnostikos sistemos adaptavimo įvairių ūkio sektorių įmonėms ir kintančioms aplinkos sąlygoms galimybės. Reikšminiai žodžiai: įmonių būklės analizė ir vertinimas, bankroto grėsmės diagnostika, integruoto vertinimo modelis, santykiniai finansiniai rodikliai, absoliutiniai finansiniai rodikliai.